The Impact of Online Education: An Analysis of the Effects of Distance Learning on Students’ Motivation - Ghina Rhoudotul Jannah; Salsabila Nasution (Era Scientific Publisher, 2026)
In online learning environments, student motivation has emerged as a major challenge, as learners are required to be more independent and manage their own time effectively. Nevertheless, online education also presents positive aspects. Students who are familiar with digital technology and appreciate time flexibility often demonstrate higher levels of learning motivation. Digital platforms provide opportunities for teachers to design learning activities that are varied, interactive, and adaptive, which may enhance students’ interest and engagement in the learning process. This study aims to examine how distance learning influences students’ learning motivation by considering several key factors, including digital interaction, motivation, learning satisfaction, the use of online platforms, environmental support, and technical constraints encountered during the implementation of online learning. The research employed a literature review method with a descriptive-analytical approach to explore empirical findings related to the impact of distance learning on student motivation. This method was selected to collect, analyze, and synthesize data from ten academic journal articles published during the COVID-19 pandemic. The reviewed articles addressed themes such as online learning, learning motivation, teacher–student interaction, learning satisfaction, digital platform utilization, educational policies, and challenges in implementing distance learning at both school and higher education levels. Data were obtained through searches in academic databases and repositories, including Google Scholar, ResearchGate, and institutional journal portals. Overall, the findings indicate that online learning remains less effective due to various challenges, such as limited internet connectivity, inadequate learning devices, low student motivation, and minimal interaction between teachers and students. As a result, students’ learning satisfaction, academic achievement, and learning character tend to decline, suggesting that distance learning has not yet been able to fully replace face-to-face instruction.